Gut epithelial barrier and systemic inflammation during chronic HIV infection. (2nd January 2015) - Somsouk, Ma; Estes, Jacob D.; Deleage, Claire; Dunham, Richard M.; Albright, Rebecca; Inadomi, John M.; Martin, Jeffrey N.; Deeks, Steven G.; McCune, Joseph M.; Hunt, Peter W.
Abstract : Objective: Microbial translocation and innate immune action characterize HIV infection. Continued gut mucosal dysfunction during treatment and its relationship to CD4 + T-cell recovery has not been well described. Design: A cross-sectional study was performed of antiretroviral therapy (ART)-suppressed (immunologic responders with CD4 + > 500 cells/μl and immunologic nonresponders with CD4 + < 350 cells/μl), untreated HIV-infected, and seronegative participants consenting to gut biopsies and a blood draw. Methods: Neutrophil infiltration as a surrogate response to epithelial breach, colorectal epithelial proliferation as a measure of repair, and mucosal apoptosis by immunohistochemistry were determined in gut biopsies. Plasma markers of monocyte activation (sCD14), immune activation (interleukin-6), and indoleamine 2, 3-dioxygenase-1 activity (plasma kynurenine/tryptophanratio) were concurrently measured. Results: Each HIV-infected group had greater neutrophil infiltration than controls. Similarly, untreated HIV-infected participants and ART-suppressed immunologic responders had increased epithelial proliferation compared with controls, but immunologic nonresponders had no appreciable increase in epithelial proliferation despite elevated neutrophil infiltration. The CD4 + T-cell count was positively correlated with epithelial proliferation and was modestly negatively correlated with neutrophil infiltration in ART-suppressed patients. Epithelial proliferation was inversely correlated with mucosal apoptosis, and apoptosis was linked to plasma sCD14 and modestly to kynurenine/tryptophan ratio. Conclusions: Neutrophil infiltration and mucosal apoptosis remain abnormally high despite ART. Epithelial proliferation increases in HIV, but may be impaired in immunologic nonresponders. Whether mucosal apoptosis is a cause or consequence of epithelial proliferative defects is unclear, but appears to be associated with systemic inflammation. The impact of ART and interventions targeting the gut epithelial barrier in treated HIV infection warrant further investigation. Abstract : Supplemental Digital Content is available in the text